2013
DOI: 10.1080/10911359.2013.772462
|View full text |Cite
|
Sign up to set email alerts
|

Going Along to Get Along? Interpersonal Processes and Girls' Delinquency

Abstract: Although social development research indicates that affiliation with delinquent peers predicts adolescent delinquent behavior, less is known about how peer relationships may impact girls' delinquent behavior differently than boys' behavior. To address this gap, this study examines adjudicated girls' perceptions of how their peer relationships impacted their decisions to engage in delinquency. Through in-depth, semi-structured interviews, a sample of eight adjudicated girls shared their perceptions of how same-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…According to these theories, delinquent behavior is learned in three major ways: through exposure to criminal models whose behavior is imitated, through reinforcement of delinquency, and through teaching of beliefs that promote delinquency. Empirical findings support the connection between peers' delinquency and the youths own delinquent behavior, where deviant peers both expose youths to criminal activities as well as encourage such behavior (Brauer and De Coster, 2015;Farrington, Ttofi & Coid, 2009;Haynie, 2002;Warr, 2002;Wike, Miller, Winn, & Taylor, 2013;Worthen, 2012). Meta analyses of the predictors of juvenile delinquency have found that deviant peers are a major risk factor for adolescents (Wong, Slotboom, & Bijleveld, 2010), and a deviant peer group has been shown to be one of the strongest predictors of female delinquency (Hubbard & Pratt, 2002), even when parents, school and other interpersonal factors are controlled for (Pleydon & Schner, 2001).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…According to these theories, delinquent behavior is learned in three major ways: through exposure to criminal models whose behavior is imitated, through reinforcement of delinquency, and through teaching of beliefs that promote delinquency. Empirical findings support the connection between peers' delinquency and the youths own delinquent behavior, where deviant peers both expose youths to criminal activities as well as encourage such behavior (Brauer and De Coster, 2015;Farrington, Ttofi & Coid, 2009;Haynie, 2002;Warr, 2002;Wike, Miller, Winn, & Taylor, 2013;Worthen, 2012). Meta analyses of the predictors of juvenile delinquency have found that deviant peers are a major risk factor for adolescents (Wong, Slotboom, & Bijleveld, 2010), and a deviant peer group has been shown to be one of the strongest predictors of female delinquency (Hubbard & Pratt, 2002), even when parents, school and other interpersonal factors are controlled for (Pleydon & Schner, 2001).…”
Section: Introductionmentioning
confidence: 88%
“…The females in the study also expressed a strong sense of personal agency and efficacy in making their own decisions, mostly denying being influenced by peers and partners to engage in delinquent acts. However, in depth analyses of the material revealed that the girls did in fact describe instances where they were influenced (Wike et al, 2013). Another qualitative study found that the gender of peers, from the young females' perspective, can have different influence on their delinquency (Solomon, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although girls who disengage or display deviant behavior may not consider that their decision making may have been influenced by their peers, the manifestation of such behavior can be considered as protective at times (Wike et al, 2013). Disengagement from school among females tends to be passive as opposed to acted out (Symonds et al, 2014).…”
Section: Re/engagement Marginalization and Liberationmentioning
confidence: 99%
“…Disengagement from school among females tends to be passive as opposed to acted out (Symonds et al, 2014). Indeed, it has been argued that interventions which utilize the strength of close friendships and acknowledge the positive aspects of such deviant behavior may generate successful engagement (Wike et al, 2013). This has particular implications for female students within the Irish context where 43% of students identified as at-risk or marginalized are female (Smyth et al, 2015).…”
Section: Introductionmentioning
confidence: 99%